Bi-compartmental communication contributes to the opposite proliferative behavior of Notch1-deficient hair follicle and epidermal keratinocytes - Lee, Jonghyeob (2007)
Notch1-deficient epidermal keratinocytes become progressively hyperplastic, eventually producing tumors. In contrast, we observed that Notch1 deficient hair matrix keratinocytes have lower mitotic rates, resulting in smaller follicles with fewer cells. In addition, the ratio of melanocytes to keratinocytes is greatly reduced. Investigation into the underlying mechanistic basis for these phenotypes revealed that three pathways, not previously linked with Notch signaling, were significantly impacted: the KIT, TGFβ and IGF signaling pathways. The level of Kitl/Scf produced by follicular keratinocytes was reduced, resulting in a decline of resident melanocyte populations. TGFβ ligands were elevated in Notch1-deficient keratinocytes, which correlated with elevated expression of several targets, including the diffusible IGF antagonist IGFBP3 in the dermal papilla. Diffusible stromal targets remained elevated in the absence of epithelial TGFβ receptors, consistent with paracrine TGFβ actions. Overexpression of IGF1 in the keratinocyte reversed the phenotype, as expected if Notch1 loss altered the IGF/IGFBP equilibrium. Conversely, epidermal keratinocytes contained less stromal IGFBP4 and may thus be primed to experience an increase in IGF signaling as animals age. These results suggest that Notch1 participates in a bi-compartmental communication system that controls homeostasis, follicular proliferation rates and melanocyte population via modulation of KIT, TGFβ and IGF signaling.